Paper : paging through history - Kurlansky, Mark (New York : W.W. Norton & Company, 2016)
Presents a history of paper and the unexpected ways it shaped a modern world transitioning toward digital technologies, tracing the role of paper and papermaking in education, media, religion, commerce, and art.
Includes bibliographical references and index.
Keywords: Paper -- History; Papermaking -- History; Paper industry -- History; Paper -- History; Papermaking -- History; Paper industry -- History